SPEECH STYLE OF MALE AND FEMALE CUSTOMERS IN MAKING COMPLAINTS AT TELKOM INDONESIA BANYUWANGI - ARIFIN, GUSTI PINANDHITA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: speech style, gender, complaint, Telkom Indonesia Language is the most important part of the society to communicate. The way or style when people speak is called as speech style. The writer conducted a study about speech style used by the customers of Telkom Indonesia Banyuwangiwhen they complain to the customer service. The purposes of this study are toinvestigate the types of language styles used by male and female customers when they complain their problems and the possible reasons behind the language styles used by the customers of Telkom Indonesia Banyuwangi.This study used qualitative approach in purpose to the use of clear and systematic description about the data being observed. Descriptive study in textual analysis is used in this study to analyze the conversation of the customers Telkom Indonesia Banyuwangi This study found that there were three kinds of speech style used by male and female customers of Telkom Indonesia Banyuwangi, such as formal style, consultative style and casual style. The data showed that the most dominant style used by the customer was casual style.This study found that only male customer who used formal style when they delivered their complaints, while female customers did not use it. This study also found there were four reasons behind certain styles used, such as social background, age of addressee, speech convergence and speech divergence. Social background and age of the addressee became the most dominant reasons used by the customers of Telkom Indonesia Banyuwangi.The writer hoped that this study can be the guidance for the next researchers who want to conduct the same study. The writer also suggested to the next researchers to conduct researches about speech style in different features orobjects.